KUTU PUTIH SINGKONG, PHENACOCCUS MANIHOTI MATILE-FERRERO (HEMIPTERA: PSEUDOCOCCIDAE): PERSEBARAN GEOGRAFI DI PULAU JAWA DAN RINTISAN PENGENDALIAN HAYATI - Abduchalek, Budi; Rauf, Aunu; ., Pudjianto (Universitas Lampung, 2017)
Cassava mealybug, Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae): Geographic distribution in Java and initiation of biological control. Cassava mealybug, Phenacoccus manihoti Matile-Ferrero (Hemiptera: Psedococcidae), is a recently introduced pest in Indonesia. Parasitoid Anagyrus lopezi (De Santis) (Hymenoptera: Encyrtidae) was imported to control the pest. Studies were conducted to determine geographic distribution of P. manihoti throughout Java, and to evaluate the potential of the parasitoid as a biological control agent. Geographic distribution of the pest was determined through field survey, whereas evaluation of the parasitoid was studied through cage experiment and field release. Our survey revealed that the cassava mealybug has spread throughout Java. Heavy infestations caused shortened and distorted stems, complete defoliation, and stunted growth. In cages containing only mealybugs, all cassava plants (100%) died after two months. Whereas in cages containing both mealybugs and three pairs of parasitoid, rate of parasitization was 25% and plant mortality 20%. Parasitoids released in the field were able to survive, reproduce, and establish under Bogor climatic condition. These might indicate that parasitoid A. lopezi is a potential natural enemy to be used in biological control program of the cassava mealybug.